Distribution of lymphocyte subpopulations of goats experimentally infected with wild lineages VD57 and attenuated T1 of Corynebacterium pseudotuberculosis in response to secret antigens (TPP and MQD) from the attenuated lineage (Research, Society and Development, 2022)
Caseous lymphadenitis is a chronic infectious disease of small ruminants, goats and sheep, causing great economic losses, characterized by the formation of subcutaneous granulomas and in internal organs whose etiologic agent is Corynebacterium pseudotuberculosis, Gram-positive bacillus, and facultative intracellular pathogen of phagocytes. , phylogenetically related to Mycobacterium tuberculosis. This study aimed to evaluate "in vitro" the phenotypes of subpopulations of cells of the peripheral blood leukocyte lineage of goats experimentally infected with the T1 and VD57 strains of Corynebacterium pseudotuberculosis, being the cells stimulated with secreted/excreted antigens of the T1 strain using as tool the flow cytometry technique. The expression of CD4 cells is higher in animals infected with the VD57 lineage under both TPP and MQD antigenic stimuli. The expression of CD8-labeled cells is higher in the group of animals infected with the T1 lineage for both stimuli with increasing expression over time. For the CD21 marker there was greater expression in the group of animals infected with the T1 lineage, however in the group of animals infected with the VD57 lineage there was significant expression at 60 days of infection. There was no difference in the proliferation index of TCRgd cells under the stimulus of the two antigens in the group infected with T1, while in the group infected with the VD57 lineage; the TPP antigen had a higher proliferation index at 60 days of infection. It can be observed that there were differences in the expression of the cell phenotype in peripheral blood cells of the animals infected with the T1 and VD57 strains and stimulated with the TPP and MQD secreted antigens; however, the TPP antigen proved to be the greatest inducer of cell proliferation. Both strains demonstrated significant indices in cell proliferation.